Isichazamazwi SesiNdebele as Reflector of the Moral and Ideological Values of Society - Moyo, Nobuhle (Lexikos, 2007)
Abstract: Isichazamazwi SesiNdebele (henceforth the ISN) reflect the moral and ideological values of society. This article analyses the ISN as reflector of the moral and ideological values of the Ndebele society. The ISN highlights fundamental beliefs and ideas of the Ndebele people. The study stems from the observation that the culture of a people will always reflect in a dictionary as culture and language are inextricably intertwined. The aim of this article is to discuss the ways in which the ISN reflects the moral and ideological values of society. The article examines how the society in which the dictionary was created influenced the choice of lemmas and the phrasing of definitions. The focus is on sexist definitions, terms referring to ethnic groups and the treatment of taboo words and religious terms. These terms denote cultural attitudes harboured by the Ndebele society. The article discusses how the treatment of these terms reflects on the values prevalent in the culture of the Ndebele community.Keywords: MONOLINGUAL DICTIONARY, DEFINITIONS, LANGUAGE, CULTURE, TABOO WORDS, IDEOLOGICAL VALUES, SEXIST ATTITUDESOpsomming: Isichazamazwi SesiNdebele as reflekteerder van die morele en ideologiese waardes van die gemeenskap. Isichazamazwi SesiNdebele (voortaan die ISN) weerspieël die morele en ideologiese waardes van die gemeenskap. Hierdie artikel ontleed die ISN as reflekteerder van die morele en ideologiese waardes van die Ndebelegemeenskap. Die ISN belig fundamentele beskouings en opvattings van die Ndebelevolk. Die studie spruit voort uit die waarneming dat die kultuur van 'n volk altyd in 'n woordeboek weerspieël sal word omdat kul-tuur en taal onlosmaaklik vervleg is. Die doel van die artikel is om die maniere te bespreek waarop die ISN die morele en ideologiese waardes van die gemeenskap reflekteer. Die artikel ondersoek hoe die gemeenskap waarin die woordeboek tot stand gekom het die keuse van lemmas en die bewoording van definisies beÃ¯nvloed het. Die fokus is op seksistiese definisies, terme wat na etniese groepe verwys en die behandeling van taboewoorde en godsdienstige terme. Hierdie terme dui kulturele ingesteldhede aan wat deur die Ndebelegemeenskap gekoester word. Die artikel be-spreek hoe die behandeling van hierdie terme waardes reflekteer wat in die kultuur van die Nde-belesamelewing gangbaar is.Sleutelwoorde: EENTALIGE WOORDEBOEK, DEFINISIES, TAAL, KULTUUR, TABOE-WOORDE, IDEOLOGIESE WAARDES, SEKSISTIESE INGESTELDHEDE